T-cell lymphoma secondary to checkpoint inhibitor therapy. Issue 1 (28th February 2020) - Anand, Kartik; Ensor, Joe; Pingali, Sai Ravi; Hwu, Patrick; Duvic, Madeleine; Chiang, Stephen; Miranda, Roberto; Zu, Youli; Iyer, Swaminathan
Abstract : Background: Murine model suggests programmed cell death-1 (PD-1), an immune checkpoint not only plays role in tumor escape but is also a tumor suppressor for T-cells. But until, no reports of secondary T-cell lymphoma postuse of immune checkpoint inhibitors (ICIs) has been reported. Herein, we present a hitherto unreported phenomenon of secondary T-cell lymphoma when PD-1 inhibitor was used in a patient diagnosed with a tumor of epithelial origin. Case report: A man in mid-70s presented with biopsy-proven metastatic tumor of epithelial origin. Patient received carboplatin in combination with paclitaxel for four cycles leading to partial remission. The patient was subsequently switched to pembrolizumab due to persistent disease in the mediastinum. After four cycles of PD-1 inhibitor, patient presented with progression of disease and was diagnosed with biopsy-proven peripheral T-cell lymphoma-not otherwise specified. Based on the reported tumor suppressor function of PD-1 in murine models, we hypothesized that the use of PD-1 inhibitor caused clonal proliferation of abnormal T-cell clone leading to T-cell lymphoma. T-cell receptor (TCR) sequencing was performed by TCRβ sequencing and T-cell clones from pre-ICI treatment specimen were compared with post-ICI treatment specimens. We show that one of the T-cell clones present in pre-ICI treatment specimen at a low frequency of had massive expansion to become most dominant clone in post-ICI treatment specimens leading to lymphoma. Moreover, targeted exome sequencing revealed a new TET2 mutation in the clone representing the lymphoma. Next, we retrospectively reviewed the Food and Drug Administration (FDA) Adverse Events Reporting System (FAERS), the pharmacovigilance database from 2012 to 2018 to find the reported incidence of this phenomenon and calculated the reporting OR (ROR) for disproportionality analysis for risk of T-cell lymphoma due to checkpoint inhibitors compared with other drugs. In FAERS, the incidence of T-cell lymphoma post-ICIs (pembrolizumab, nivolumab and ipilimumab) was found to be 0.02% with 17% mortality. The ROR probability of risk of T-cell lymphoma compared with other drugs in pharmacovigilance database was increased at 1.91. Conclusions: T-cell lymphoma is a rare sequela of ICIs with high mortality. Larger studies with long-term follow-up of patients receiving ICIs is needed.